Welfare Costs of Business Cycles in Turkey - Yilmaz, Ensar (WILEY, 2014)
How large are welfare costs related to economic aggregate fluctuations is a topic of great concern among economists at least since Lucas's (1987) model. Our analysis assesses the magnitude of such costs for Turkey by means of two approaches: aggregate and disaggregate. The former approach uses aggregate data employing three alternative trend-cycle decomposition methods which are Lucas' classical set-up with deterministic linear trend for consumption, Hodrick and Prescott filter and one in which consumption trend is stochastic and whose implementation is performed using Beveridge-Nelson decomposition. The results of both approaches suggest that Turkey has high welfare costs associated with business cycles.
Keywords: RISK PREFERENCES; FLUCTUATIONS; Business & Economics